2021
DOI: 10.1172/jci138267
|View full text |Cite
|
Sign up to set email alerts
|

Impaired complex I repair causes recessive Leber’s hereditary optic neuropathy

Abstract: Leber’s hereditary optic neuropathy (LHON) is the most frequent mitochondrial disease and was the first to be genetically defined by a point mutation in mitochondrial DNA (mtDNA). A molecular diagnosis is achieved in up to 95% of cases, the vast majority of which are accounted for by 3 mutations within mitochondrial complex I subunit–encoding genes in the mtDNA (mtLHON). Here, we resolve the enigma of LHON in the absence of pathogenic mtDNA mutations. We describe biallelic mutations in a nuclear encoded gene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
130
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(140 citation statements)
references
References 49 publications
(93 reference statements)
8
130
1
Order By: Relevance
“…Similarly, families with autosomal recessive LHON (arLHON), which is not maternally transferred, have been found to carry mutations in the nuclear-encoded gene, DNAJC30 . DNAJC30 has been implicated as a chaperone protein that shuttles damaged subunits of Complex I away for turnover [ 183 ]. With these links to Complex I, it is not surprising that the underlying pathology of LHON has been suggested to be tied to inadequate ATP generation and increased ROS production, both due to inefficient electron/proton transport across the MIM.…”
Section: The Role Of Mitochondria In Optic Nerve and Rgc Pathologymentioning
confidence: 99%
“…Similarly, families with autosomal recessive LHON (arLHON), which is not maternally transferred, have been found to carry mutations in the nuclear-encoded gene, DNAJC30 . DNAJC30 has been implicated as a chaperone protein that shuttles damaged subunits of Complex I away for turnover [ 183 ]. With these links to Complex I, it is not surprising that the underlying pathology of LHON has been suggested to be tied to inadequate ATP generation and increased ROS production, both due to inefficient electron/proton transport across the MIM.…”
Section: The Role Of Mitochondria In Optic Nerve and Rgc Pathologymentioning
confidence: 99%
“…Assembly of protein complexes [70] or even further association of several protein complexes require a coordinated process with the help of chaperons also called assembly factors. In recent years, classical CP became a very popular tool to study the significance of individual subunits and assembly factors of the OXPHOS complexes in bacteria [39,40,61] and mitochondria from mammals [17,21,22,27,28,36,[41][42][43][44][45][46][47][48][49][50]53,[64][65][66] and plants [54][55][56][57]60,62].…”
Section: Assembly and Stability Of Oxphos Complexesmentioning
confidence: 99%
“…Introducing SILAC as a pulse [74] for several hours followed by CP workflow gives insights into dynamics within protein complexes. This strategy enables the study of remodeling and repair in protein complexes [19,66]. Of mention in that respect is an experiment carried out in differentiated mouse myotubes from C2C12 cells (Figure 2).…”
Section: Turnover Of Subunits Within Protein Complexesmentioning
confidence: 99%
“…DNAJC30 interacts with the mitochondrial ATP synthase machinery and facilitates ATP synthesis as well as acting as a chaperone in exchanging defective complex 1. 14,21 Studies have shown that the gender difference could be attributed to the metabolic regulation of oestrogens that directly or indirectly regulate mitochondrial metabolism. 22,23 Furthermore, recent studies have documented that X-linked nuclear modifiers (PRICKLE3, a mitochondrial protein linked to biogenesis of ATPase) modify the phenotypic manifestation of LHON.…”
Section: Lhonmentioning
confidence: 99%